2020
DOI: 10.1038/s41598-020-76541-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and pathogenicity of H6 avian influenza viruses isolated from Southern China during 2011 to 2017 in mice and chickens

Abstract: H6 subtype avian influenza viruses spread widely in birds and pose potential threats to poultry and mammals, even to human beings. In this study, the evolution and pathogenicity of H6 AIVs isolated in live poultry markets from 2011 to 2017 were investigated. These H6 isolates were reassortant with other subtypes of influenza virus with increasing genomic diversity. However, no predominant genotype was found during this period. All of the H6N2 and most of the H6N6 isolates replicated efficiently in lungs of ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…Our results showed that, even though there was no evidence of clinical signs of disease compatible with IAV infection, both viruses infected chickens (observed mainly by seroconversion) but were not transmitted to other birds through direct contact. This, together with the significant bursa-to-body weight ratios reduction observed in both infected groups, demonstrated that WT557/H6N2 and 20Ch557/H6N2 viruses behave like LPAIV in chickens as observed with viruses from other lineages (Spackman et al, 2010;Daoust et al, 2011;Pantin-Jackwood et al, 2017;Lin et al, 2020). There is evidence similar to ours, where the low viral shedding by the cloaca observed after infection with LPAIV significantly reduces virus transmission among birds (Ruiz-Hernandez et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Our results showed that, even though there was no evidence of clinical signs of disease compatible with IAV infection, both viruses infected chickens (observed mainly by seroconversion) but were not transmitted to other birds through direct contact. This, together with the significant bursa-to-body weight ratios reduction observed in both infected groups, demonstrated that WT557/H6N2 and 20Ch557/H6N2 viruses behave like LPAIV in chickens as observed with viruses from other lineages (Spackman et al, 2010;Daoust et al, 2011;Pantin-Jackwood et al, 2017;Lin et al, 2020). There is evidence similar to ours, where the low viral shedding by the cloaca observed after infection with LPAIV significantly reduces virus transmission among birds (Ruiz-Hernandez et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Our results showed that, even though there was no evidence of clinical signs of disease compatible with IAV infection, both viruses infected chickens (observed mainly by seroconversion) but were not transmitted to other birds through direct contact (measured by virus detection from swabs and seroconversion). This, together with the significant bursa-to-body weight ratios reduction observed in both infected groups, demonstrated that WT557/H6N2 and 20Ch557/H6N2 viruses behave like LPAIV in chickens as observed with viruses from other lineages 15–17 . Our study showed that both viruses were detected in trachea and cloaca of infected chickens at 1 and 3 dpi, but only 20Ch557/H6N2 virus was detected in trachea and cloaca of infected chickens till day 7 post-infection.…”
Section: Discussionsupporting
confidence: 58%
“…On the other hand, the H6 was identified in two different species, in a whimbrel and in a Franklins’ gull. Interestingly, domestic poultry has been reported to be extremely susceptible to this subtype [ 35 ], representing an economic and social threat. H6 segment has been intensely identified in mallard from Canada and presents global distribution.…”
Section: Discussionmentioning
confidence: 99%